CULTIVATE LITERACY THROUGH ONE WEEKLY FAIRY TO IMPROVE MORAL BEHAVIOR IN ELEMENTARY SCHOOL CHILDREN - Parmila, Wisa; Amanda, Wahida Nur; Wulandari, Wina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
Children's moral behavior at this time is very threatened and has been somewhat reduced. It should be that behavior or character is educated early. The role of children's reading in the formation of early childhood moral behavior is very important. Likewise, the role of moral education is needed by the government as the basis for education in Indonesia. Therefore, this study aims to explore the values of moral education in fabled fairy tales and their role in the personal formation of children of primary school age. Literary works should be introduced to the child from an early age. This aims to develop literacy skills so that the habit of imagining and creating is created. literacy is widely interpreted as language skills that include the ability to listen, speak, read, and write, as well as the ability to think which is an element in it. The method used is qualitative descriptive research with content analysis techniques. Data sources come from media, journals, and books. The value of character education found in the fairy tale